Increasing Effects of Selective 5-Hydroxytryptamine Type 2C Receptor Stimulation on Evoked Momentary Urethral Closure in Female Rats and Humans - Kamo, Izumi; Nagata, Hiroshi; O’Connell, Gale; Kato, Takuya; Imanishi, Akio; Kuno, Masako; Okanishi, Satoshi; Yoshikawa, Kyoko; Nishiyama, Yuya (The Journal of pharmacology and experimental therapeutics, 2021)
Under healthy conditions, more than one urethra-closing reflex, including both bladder afferent–independent and –dependent actions, function during momentary elevation of intravesical (bladder) pressure to prevent urinary incontinence. In the current study, the effects of a novel selective 5-hydroxytryptamine type 2C (5-HT2C) receptor agonist, TAK-233, on evoked momentary urethra-closing functions were investigated in female rats and humans to elucidate 5-HT2C receptor functions. In anesthetized female rats, TAK-233 dose-dependently and significantly increased urethral resistance during sneezing in rats with distended vaginas and bilaterally transected pelvic nerves. The drug also dose-dependently and significantly increased urethral resistance during momentary intravesical pressure elevation by electrical stimulation of abdominal muscles in rats with a transected spinal cord at the T8–T9 level and intact pelvic nerves. The increased effects observed during electrical stimulation were abolished by either an intravenously administered selective 5-HT2C receptor antagonist, SB 242084, or bilateral transection of the pelvic nerves or somatic nerves innervating the external urethral sphincter and pelvic floor muscles. In the spinal cord–transected and pelvic nerve–intact rats, TAK-233 enlarged the urethra-closing responses induced by both passive and abrupt intravesical pressure elevation, measured by a microtip transducer located in the middle urethra. Additionally, the effects of TAK-233 on the stimulus threshold of urethral contractile responses induced by transcranial magnetic stimulation were investigated in healthy female volunteers. The drug dose-dependently and significantly lowered this stimulus threshold, indicating an increased sensitivity of the response. These results demonstrate that 5-HT2C receptor stimulation enhances the evoked momentary urethra-closing functions in both female rats and humans. 5-hydroxytryptamine (serotonin) type 2C (5-HT2C) receptor stimulation by TAK-233 enhanced urethral resistance in rats during an evoked momentary event in which the bladder afferent–independent or –dependent reflex functions via striated muscle–mediated mechanisms. The increases in sensitivity of transcranial magnetic stimulation–evoked urethral contractile responses in healthy female subjects indicates that this mechanism also functions in humans. The evoked momentary conditions activating these reflexes provide a suitable model to demonstrate the effects of 5-HT2C receptor stimulation.